Integrating Information Technology and Investigation in Forensic Auditing: Case Study of Structured Fraud PT XXX - Sofyan, Riski; Renaldi, Yandi; Yanti, Harti Budi (E-Jurnal Akuntansi, 2026)
Structured fraud exploits information asymmetry in decentralized organizations. This study examines how integrated forensic auditing and information technology uncover fraud networks and the effectiveness of combining digital evidence with physical verification. A multiple case study analyzes two fraud incidents at PT XXX's Semarang and Lampung branches. Data from interviews, digital evidence (WhatsApp chats, photos, ERP logs), and documents were analyzed thematically using the Miles and Huberman model with NVivo 12 support. Findings reveal contrasting fraud patterns: authority-based Marketing Cost manipulation in Lampung versus collaborative asset theft networks in Semarang. Information technology served dual roles, enabling fraud while providing crucial investigation tools like “Get Contact” for identity tracing and WhatsApp metadata for chronology reconstruction. The investigation successfully integrated digital analysis with physical verification, demonstrating an effective hybrid forensic model for mapping hidden relationships and fraud schemes. The study concludes that combating structured fraud requires hybrid investigations synergizing digital forensics with physical auditing to enhance detection accuracy. Practical implications include strengthening IT-based internal controls, developing digital forensic competencies, and establishing standards for digital evidence in fraud investigations.